Enhanced neutrophil activity, but not neutrophil extracellular trap markers, is found in patients with symptomatic chronic peripheral arterial disease. (3rd October 2022) - Buso, G; Faggin, E; Bressan, A; Galliazzo, S; Cinetto, F; Felice, C; Fusaro, M; Erdmann, A; Pauletto, P; Rattazzi, M; Mazzolai, L
Abstract: Background/Introduction: Neutrophil degranulation and neutrophil extracellular traps (NETs) are suggested to play a role in cardiovascular (CV) disease development [1]. Human studies showed that markers of NETs, are increased in patients with severe coronary atherosclerosis and predict risk of cardiac events [2]. The role of NETs in peripheral artery disease (PAD) has not been investigated. Purpose: To measure circulating markers of neutrophil activity in patients with symptomatic PAD compared with matched healthy controls, evaluate their association with disease severity, and assess their prognostic value. Methods: Multicenter, prospective case-control study. Circulating levels of polymorphonuclear neutrophil (PMN)-elastase, neutrophil gelatinase-associated lipocalin (NGAL), myeloperoxidase (MPO), and NETs-associated MPO-DNA complexes were measured in patients with symptomatic PAD and heathy controls. The former underwent comprehensive vascular evaluation including ankle-brachial index (ABI) calculation, transcutaneous oximetry measurement, constant-load treadmill test, 6-minute walking test, pulse wave velocity, and flow-mediated dilatation of the brachial artery. Six-month outcomes were: occurrence of major adverse CV (MACE) and limb events (MALE), ABI reduction ≥0.15, and 6-minute walking distance reduction ≥20 m. Results: Overall, 110 participants were included, 66 had symptomatic PAD. Levels of all but one biomarker (MPO-DNA) were significantly higher in patients with PAD compared with healthy controls (Fig. 1). No significant correlation was found between biomarkers and vascular tests in patients with PAD. Baseline PMN-elastase (adjusted hazard ratio [HR]: 1.010; 95% CI: 1.000–1.020; p=0.040) and MPO (adjusted HR: 1.027; 95% CI: 1.004–1.051; p=0.019) were predictive of MACE and/or MALE at 6-month follow-up in patients with symptomatic PAD (Table 1). Conclusions: Present data show enhanced neutrophil activity, but not NETs levels, in patients with symptomatic PAD compared to controls. Baseline PMN-elastase and MPO levels were associated with worst CV outcome in patients with chronic PAD. These data suggest a role of neutrophils in PAD development and severity that needs to be further elucidated. Funding Acknowledgement: Type of funding sources: None.